PENGARUH TINDAKAN KESIAPSIAGAAN TERHADAP PARTISIPASI MASYARAKAT DALAM TANGGAP DARURAT BANJIR DI KECAMATAN RANGKASBITUNG - Ajeng Prihantini; Henita Rahmayanti; Samadi Samadi (Jurnal Pensil : Pendidikan Teknik Sipil, 2022)
Every disaster brings victims, both human and property is a fact. But whatever the type of disaster, there is always an omen before it comes. This is where the urgency is to understand every sign that comes correctly and accurately. So, of course, knowledge, skills, and skills are needed on how the community, especially in disaster-prone areas, prepares anticipatory steps for the arrival of the disaster (Priyowidodo and Luik 2013). The readiness and skills of the community, especially families, are the primary keys to safety in dealing with disaster emergencies (Willem Rampangilei 2018). This study aims to determine the effect of preparedness measures on community participation in flood emergency response. This research uses research that uses correlational survey method. In this study, the independent variable is community participation in disaster emergency response, while the dependent variable is preparedness measures. This study aimed to determine the effect of preparedness measures on community participation in flood emergency response. The results of the survey: Preparedness measures (X) affect the community participation variable (Y) by 16%.